Printed circuit board design using AutoCAD - Schroeder, Chris, 1954- (EDN series for design engineers.)
Designing PCBs is made easier with the help of today's sophisticated CAD tools, but many companies' requirements do not justify the acquisition cost and learning curve associated with specialized PCB design software. Printed Circuit Board Design Using AutoCAD helps design engineers and students get the most out of their AutoCAD workstation, showing tips and techniques to improve your design process. The book is organized as a series of exercises that show the reader how to draft electronic schematics and to design single-sided, double-sided, and surface-mount PCBs. Coverage includes drafting s.